Decomposition of δ-Continuity and δ^*-Continuity - Powar, PL; Dubey, Pratibha (International Journal of Computer Sciences and Engineering, 2025)
In the present paper, the notion of δ-open sets, g-closed sets, δg-closed sets; and the relation between them has been studied. It is also noted that the collection of δ-open sets form the topology. A new concept of δ^*-continuity has been established which is a generalization of the classical form of continuity. By introducing the idea of δ-fine ope n set and δg-fine open set, δ-fine continuity and δg-fine continuity have been defined. In support of these new concepts, several illustrative examples have been given.